Extreme Sports Medicine - Feletti, Francesco (Springer International Publishing : Imprint: Springer, 2017)
This technically oriented book on medicine as applied to extreme sports offers broad coverage of the field extending well beyond the usual focus on major trauma and acute injuries. In addition to the injuries and diseases associated with individual extreme sports, this book also addresses the topics of psychology, dermatology, ophthalmology, infectious diseases, physiology, nutrition, training, injury prevention strategies, rehabilitation, doping, treatment in hostile environments, and legal aspects. Innovative and less frequently considered topics are also discussed, such as recent advances in protective equipment and materials, the effects of exposure on whole-body vibration, and cold exposure risk management. More than 60 of the most authoritative experts from across the world have contributed to this book, drawing on their personal experiences and including practical examples whenever relevant. Both subject matter and illustrations have been selected with the utmost care, the latter including photographs of world-class athletes.The book's multidisciplinary approach to the subject ensures that it will be relevant to a wide readership.
Keywords: Medicine.; Orthopedics.; Sports medicine.; elektronické knihy; electronic books